POLA KONSUMSI INFORMASI MELALUI MEDIA DI KALANGAN GENERASI Z (Studi terhadap SMAN 4, SMAN 9, SMA Mardisiswa, dan SMA Al-Azhar 14 di Kota Semarang) - Krisan Putri, Florentina; Manalu, S. Rouli; Suryanto Gono, Joyo Nur (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Differing from its predecessors that tend to have conventional media, Generation Z tends to choose digital media especially social media to obtain information. This study aims to get explanations behind the shifting pattern of such media access. Specifically this study aims to reveal the kinds of information accessed, the using patterns of digital and conventional medias, and the reasons behind Generation Z's choices of media. This research uses the theory of information consumption patterns and the Uses and Gratifications theory by Katz, Blumer, and Gurevitch. This study employs a mixed-methods of quantitative and qualitative in a sequential explanatory strategy. A survey takes 400 students of four high school of Semarang city is followed by a series of Focus Group Discussion (FGD) involving 20 students chosen purposively out of the respondents. The results show that Generation Z tends to access information through digital media, particularly through social media platforms like Instagram, TikTok, and YouTube. The main topics of information sought by Generation Z, in order, are entertainment, health, and education. Generation Z tends to use search and exploration features on digital media to obtain information efficiently and effectively. These findings align with the Uses and Gratifications theory, which emphasizes media selection based on users' specific needs.